LHC Signals of the Next-to-Lightest Scalar Higgs State of the NMSSM in the 4τ Decay Channel - M. M. Almarashi (Advances in High Energy Physics)
We study the a1a1 and Za1 decay channels of the next-to-lightest CP-even Higgs boson h2 of the NMSSM at the LHC, where the h2 is produced in gluon fusion. It is found that while the h2 discovery is impossible through the latter channel, the former one in the 4τ final state is a promising channel to discover the h2 with masses up to around 250 GeV at the LHC. Such a discovery of the h2 is mostly accompanied with a light a1, which is a clear evidence for distinguishing the NMSSM from the MSSM since such a light a1 is impossible in the MSSM.